Qualitative Study of a Boundary Value Problem for a Reaction-diffusion System (Journal of Partial Differential Equations, 2020)
ln this paper, the order of magnitude and structure of nonnegative solutions for a class of R-D systems with 3 components is obtained. Especially for the case &#945_2 =&#945_3 a complete analysis is given. By using different method from [1], a simpler and more concrete sufficient condition for uniqueness and globally asymptotic stability of nonnegative solution is also obtained.
Keywords: nonnegative solutions; magnitude; reaction-diffusion system; uniqueness; globally asymptotic stability